The role of sport fishing in shaping environmental awareness among youth and developing a culture of responsible fishing - Petrovych, Yuriy (Педагогічна Академія: наукові записки, 2025)
The relevance of the study is determined by the need to strengthen the educational potential of sport amid escalating environmental challenges, increasing anthropogenic pressure on natural ecosystems, and the need to foster a responsible attitude toward the natural environment among young people. In this regard, particular importance is attached to sporting activities that combine physical activity, compliance with regulatory requirements, and direct human interaction with nature. One such activity is sport fishing, which possesses not only a competitive dimension but also a pronounced educational, ecological, and value-oriented potential. The purpose of the article is to provide a theoretical substantiation of the role of sport fishing in shaping environmental awareness among youth and in developing a culture of responsible fishing. Methods. To achieve this purpose, a set of theoretical research methods was employed, including analysis and synthesis of scholarly literature, comparison, generalization, systematization, terminological analysis, and structural-functional analysis. Results. The study found that environmental awareness among youth is a complex integrative construct encompassing cognitive, value-motivational, emotional-personal, and behavioral components. It is substantiated that sport fishing effectively shapes environmental awareness among young people, as it combines sports training, self-discipline, self-control, compliance with rules, and the practical assimilation of norms of responsible behavior in the natural environment. It is demonstrated that direct interaction with aquatic ecosystems, participation in training sessions and competitions, adherence to sports ethics, and compliance with established regulations create favorable conditions for transforming environmental knowledge into stable patterns of environmentally appropriate behavior. It is determined that important outcomes of such activity include the development in young people of an attentive attitude toward the condition of water bodies, an awareness of the value of aquatic biological resources, a willingness to comply with established rules, and the ability to align their actions with environmental appropriateness. It is established that the educational potential of sport fishing is realized through personal experience of interaction with nature, the norm-governed character of sporting activity, ethical self-regulation, and the assimilation of environmental values. It is concluded that sport fishing has considerable educational potential and can be regarded as an effective means of engaging young people in environmentally responsible interaction with the natural environment. Prospects for further research lie in developing pedagogical conditions and practical models for the use of sport fishing in environmental education for youth.